Soil carbon, nitrogen, and phosphorus stoichiometry and its influencing factors in Chinese fir plantations across subtropical China - Tong, Ran; Wu, Tonggui; Jiang, Bo; Wang, Zhigao; Xie, Binglou; Zhou, Benzhi (Frontiers in Forests and Global Change, 2023)
Soil stoichiometry acts as an important indicator of soil interior nutrient cycling and plant nutrient supply. The study of the spatial variation of soil stoichiometry and its influencing factors at the regional scale is helpful for reflecting the functioning and structuring of ecosystems. In this study, we analyzed the patterns of soil organic carbon (SOC), total nitrogen (TN), and total phosphorus (TP) stoichiometry and its influencing factors in Chinese fir (Cunninghia lanceolata (Lamb.) Hook) plantations across subtropical China. We found that the range of SOC: TN (C:N), SOC: TP (C:P), and TN: TP (N:P) ratios were 7.32-18.27, 20.15-230.48, and 2.11-15.05, with a mean value of 13.22, 83.50, and 6.05, respectively. Well-constrained correlations were found for SOC and TN, and TN and TP. Soil TN and TP contents increased with increasing altitude, whereas soil SOC: TN :TP (C:N:P) ratios decreased. Soil TP content decreased, and C:P ratio increased with increasing mean annual temperature (MAT) and annual total solar radiation (ATSR). Soil C:N:P ratios increased with increased mean annual precipitation (MAP) and annual evaporation (AE). Overall, our findings suggested soil elements were in a state of relatively adequate supply and healthy nutrient cycling. Soil stoichiometry was affected by geographical and climatic variables to different degrees.